227. Provider Education Paired With Peer Comparison Demonstrates Sustained Reduction in Overall Antibiotic Prescribing Within a Veterans Affairs Primary Care System. (26th November 2018) - Buehrle, Deanna J; Shively, Nathan R; Clancy, Cornelius J; Decker, Brooke K
Abstract: Background: Data on antimicrobial stewardship (AS) interventions in outpatient primary care settings and optimal strategies to sustain results are lacking. We report results of a comprehensive outpatient AS intervention that included provider education and peer comparison. Methods: Baseline antibiotic prescribing data from primary care clinics at VA Pittsburgh Healthcare System from January to April 2016 were collected. Educational sessions were offered to all primary care providers (PCPs) in December 2016. During an intervention period from January to April 2017, PCPs were emailed monthly comparisons of their antibiotic prescribing rate, peer rates, and a system target. Postintervention overall antibiotic prescribing rates from January to April 2018 were assessed. The decision-support software was updated after the intervention to reflect AS team guidance. Results: During the postintervention period, 626 antibiotic prescriptions were written by 73 PCPs caring for 40, 428 patients, compared with 1, 585 antibiotic prescriptions written by 65 PCPs caring for 40, 734 patients during the baseline period and 1, 131 antibiotic prescriptions written by 73 PCPs caring for 41, 191 patients during the intervention period ( P = 0.0002). There were significantly fewer antibiotic prescriptions written during the intervention period than the baseline period ( P = 0.0286), and during the postintervention period than the intervention period ( P = 0.0286). Azithromycin use decreased by 45.9% (458 vs. 248 prescriptions, P < 0.0001) from the baseline to the intervention period and further decreased by 51.2% (248 vs. 121 prescriptions, P < 0.0001) from the intervention period to the postintervention period. Fluoroquinolone use decreased by 55.6% (160 vs. 71 prescriptions, P < 0.0001) from the baseline to the intervention period, and remained low during the postintervention period (71 vs. 72 prescriptions, P = 0.88). Conclusion: A comprehensive AS intervention including provider education and peer comparison demonstrated a sustained reduction in overall antibiotic prescribing rates among PCPs. The decision-support software may assist in maintaining reduced prescribing rates. A full data analysis to include an assessment of appropriateness during each period is ongoing. Disclosures: All authors: No reported disclosures.